2015
DOI: 10.1115/1.4031117
|View full text |Cite
|
Sign up to set email alerts
|

The Envelope of Physiological Motion of the First Carpometacarpal Joint

Abstract: Much of the hand's functional capacity is due to the versatility of the motions at the thumb carpometacarpal (CMC) joint, which are presently incompletely defined. The aim of this study was to develop a mathematical model to completely describe the envelope of physiological motion of the thumb CMC joint and then to examine if there were differences in the kinematic envelope between women and men. In vivo kinematics of the first metacarpal with respect to the trapezium were computed from computed tomography (CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 44 publications
(61 reference statements)
1
15
0
Order By: Relevance
“…This choice was particularly important to limit the radiation dose for the volunteers. Moreover, previous studies have shown that this methodology is a valid approach for the carpal kinematics evaluation …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This choice was particularly important to limit the radiation dose for the volunteers. Moreover, previous studies have shown that this methodology is a valid approach for the carpal kinematics evaluation …”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study focuses on Ex–Fl and Ab–Ad of the thumb using a rig for the standardization of the movements. We specifically chose to focus on Ex–Fl and Ab–Ad because any more complex motion of the thumb (e.g., opposition, circumduction) can be defined as a combination of these two principal motions . While we acknowledge that the use of a customized rig might lead to non‐spontaneous thumb movements, the use of a rig was necessary to standardize active thumb motion and allow comparison between participants and study groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The orientation of the axis of rotation was also described using azimuth angle ( azi ) within the radial CS reference plane, and elevation angle out of the radial CS plane (Figure 4). 43 …”
Section: Methodsmentioning
confidence: 99%
“…Thumb kinematics have mostly been investigated using surfacebased three-dimensional (3D) motion capture techniques such as high-speed video, opto-electric, electromagnetic or computed tomography (CT)-based systems (Crisco et al, 2015b;Halilaj et al, 2015;Koff et al, 2007;Kuo et al, 2002Kuo et al, , 2004Li and Tang, 2007;Miura et al, 2004;Moojen et al, 2002;Sonenblum et al, 2004;Wolfe et al, 2000). However, none of these methods allows direct evaluation of 3D (meta)carpal bone movement.…”
Section: Introductionmentioning
confidence: 99%